Yasmin Ahmad: Auteuring a New Malaysian Cinematic Landscape - Lee, Yuen Beng (Pusat Pengajian Seni, 2015)
Since P. Ramlee, no other filmmaker but Yasmin Ahmad has been capable of creating a significant impact in Malaysian cinema. She achieved this through her films that have persistently challenged not only the conventions of Malaysian cinema, but also daringly exposed societal taboos and its hypocrisies on the cinematic screen. All her six films differ from the conservative, unadventurous and conventional Malaysian films that revolve around the tiresome, "tried and tested", monotonous entertainment containing elements of love (suka), sadness (duka) and humour (jenaka). Her films, which are criticisms about the failings of the Malaysian society and in particular the Malays, employ cosmopolitan themes of humour, love and humanism to move beyond merely focusing on race and ethnicity. In doing so, her films paradoxically employ the "sensitive" issue of interethnic relations to highlight the struggles faced by common Malaysians within and between cultures and religions. By highlighting the everyday problems faced by everyday people, Yasmin Ahmad has extensively altered the Malaysian cinematic landscape by removing demarcations along racial, ethnic, religion, cultural, age and gender lines. This allows her films to move beyond being focused on multiculturalism and to contest more socially, culturally and politically issues closely related to Malaysians